Dry Suspension Formulation of Ethanol Extract from Wuluh Starfruit (Averrhoa bilimbi L.) with Arenga Gum as Suspending Agent - Zebua, Nilsya Febrika; Syafitri, Yuni; Sudewi; Novriansyah, Reza (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Wuluh starfruit (Averrhoa bilimbi L.) has a sour taste and high water content which makes the fruit easily damaged and has a short shelf life. It is necessary to process wuluh starfruit in order to obtain a product that has a longer shelf life and tastes better without reducing its benefits. The purpose of this study was to determine the wuluh starfruit in the form of ethanol extract can be formulated into a dry suspension dosage form with arenga gum as a suspension which at a certain concentration can be an optimal suspending agent. Based on the results showed that the ethanol extract of wuluh starfruit (Averrhoa bilimbi L.) could be formulated into a dry suspension. The preparation with 0.5% arenga gum as a suspending agent is the best preparation which has a moisture content of 0.46%, stationary angle of 26.48Âº, flow time of 4.77 seconds, compressibility index of 18%, particle size distribution 152.133Î¼m, viscosity 106.00 cP, pH 4.16 and sedimentation volume 0.55. Data were analyzed using SPSS 26.0 using one-way analysis of variance (ANOVA) test and post hoc Multiple Comprasions Tukey HSD test.